The Female Athlete Triad/Relative Energy Deficiency in Sports (RED-S) - Alexandra Ruivo Coelho; Gonçalo Cardoso; Marta Espanhol Brito; Inês Neves Gomes; Maria João Cascais (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract In a healthy athlete, the caloric intake is sufficient for sports energy needs and body physiological functions, allowing a balance between energy availability, bone metabolism, andmenstrual cycle.Onthe other hand, an imbalance causedby low energy availability dueto a restrictive diet, eating disorders or long periods of energy expenditure leads to multisystemic deregulation favoring the essential functions of the body. This phenomenon, described as the female athlete triad, occurs in a considerable percentage of high-performance athletes, with harmful consequences for their future. The present review was carried out based on a critical analysis of themost recent publications available and aims to provide a global perception of the topic relative energy deficit in sport (RED-S). The objective is to promote theacquisition ofmore consolidated knowledgeon an undervaluedtheme, enabling the acquisition of preventive strategies, early diagnosis and/or appropriate treatment.